Online sensor–guided hybrid ordinary differential equation–based model of nitrification dynamics in a full-scale municipal wastewater treatment plant - Guangyao Zhao; Nanami Sato; Fengjun Yin; Hong Liu; Masafumi Fujita (Bioresource Technology, 2027)

CO2 bubble-regulated porous architecture of CS@ZIF-8 microspheres for enhanced alcalase immobilization with improved walnut protein hydrolysis - Jiangjuan Yuan; Xueying Liu; Mingyao Li; Feng Jin; Baokai Cui; Jingzhen Chen; Changzhu Li; Fengjun Wang (Carbohydrate Polymers, 2026)

Effects of microbial-derived artificial humic acid on soil organic carbon stability and microbial community fractions under straw return conditions - Jiaxun Liang; Huaiyuan Teng; Le Liu; Fengjun Yang; Liqin Zhao; Bowen Fan; Jingyi Lan (Applied Soil Ecology, 2026)

Effects of taurine on microbiota composition, metabolic profiles, immune capacity, and survival of Manila Clam (Ruditapes philippinarum) larvae - Yang Liu; Kai Liao; Yang Zhang; Qi Hu; Xiaoxue He; Fengjun Xie; Lin Zhang; Zhongming Huo; Jilin Xu (Aquaculture, 2026)

Responses of aerosol optical properties and direct radiative effects to rapid shifts in anthropogenic emissions in the sichuan basin - Fengjun Shen; Jie Sun; Guiying You; Jiaxin Wei; Xinlei Lv; Qiqi Mo; Tong Liu; Miao Feng; Yanyi Feng; Shaodong Xie; Gang Zhao; Min Hu (Environmental Pollution, 2026)

Corrigendum to ’Visible light photocatalytic enhanced heterogeneous cobalt catalyzed peroxymonosulfate synergistic process to degradation atrazine: Efficiency, influencing factors, by-products removal and mechanism’[Volume 159, January 2026, Pages 166-177] - Qingkong Chen; Jieyu Xia; Fengjun Liu; Jianping Fan; Peng Yan; Mika Sillanpää (Journal of Environmental Sciences, 2026)

Methacryloxyethyl sulfobetaine (SBMA) based hydrogel with functional enhancement by acrylamide, glycerol, and thymol for strawberry preservation - Zhichao Yang; Xiaohong Guo; Ziqiang Qin; Fengjun Guo; Di Wu; Bangdi Liu; Kunsong Chen (Food Chemistry, 2026)

Controls on aeolian source dominance in an inland sand sea: Insights from the Kumtagh Sand Sea - Aimin Liang; Xiaokang Liu; Ivan Lizaga; Zhengcai Zhang; Zhizhu Su; Bo Wu; Chao Li; Fengjun Xiao; Junliang Gao; Rongliang Liu; Zhibao Dong (CATENA, 2026)

The Effect of Humic Acid From Different Raw Materials on Soil Physical and Chemical Properties and Tomato Seedling Growth - Lanjing Long; Liqin Zhao; Xiangjun Chen; Zhicheng Liu; Xue Chen; Bowen Fan; Fengjun Yang (Journal of Soil Science and Plant Nutrition, 2026)

Developing process descriptor for biological nitrogen removal in wastewater treatment - Fengjun Yin; Hao Tan; Jinjin Zheng; Zhaoming Chen; Guangyao Zhao; Di Wu; Hong Liu (Water Research, 2026)

BrNAC046 involved in hydrogen peroxide-induced leaf senescence of postharvest Chinese flowering cabbage - Fengjun Li; Baoxiang Ren; Lilang Li; Xiangjin Kong; Hanzhi Liang; Hai Liu; Ling Wang; Yueming Jiang (Postharvest Biology and Technology, 2026)

A power-free electro-Fenton process using industrial-grade iron for low-cost treatment of refractory organic wastewater - Bingjie Liu; Fengjun Yin; Hao Tan; Lin Chang; Xuehai Yue; Irene Njeri Kamau; Hong Liu (Chemical Engineering Journal, 2026)

The efficient treatment of landfill leachate using a novel osmotic microbial fuel cell system employing forward osmosis membrane featuring proton-conducting medium - Enling Tian; Fengjun Yin; Cheng Song; Ying Zhao; Hao Tan; Fuqing Zhao; Hong Liu (Water Research, 2026)

Resveratrol-Eu-layered double hydroxide nanocomposite alleviates radiation-induced lung injury through antioxidant and IL-17/NF-κB-associated anti-inflammatory effects - Fangxiao Cao; Junzhe Yang; Xiaoyi Cai; Xin Zuo; Yiming Wang; Li Du; Yuxin Lu; Xiaochen Cheng; Tingting Liu; Shan Ma; Feiyu Zhao; Shanyue Guan; et al. (Chemical Engineering Journal, 2026)

Novel diethylthiosulfinate suppresses postharvest peach brown rot in vitro and vivo by disrupting carbon metabolism and virulence pathways in Monilinia fructicola - Longshen Wang; Hui He; Ming Zhang; Chenxia Liu; Jinglin Zhang; Qiankun Wang; Liqing Zhang; Fengjun Guo; Yuanqing Liu; Huali Lin; Yongjin Qiao; Hongru Liu (International Journal of Food Microbiology, 2026)

Amplified radiative effects of coated black carbon aerosols over the Tibetan Plateau - Jie Sun; Gang Zhao; Jinyuan Yu; Weili Lin; Yi Chen; Chunxiang Ye; Wenxu Fang; Wenhao Zhou; Baifeng Zhu; Jiawei Yang; Zhijun Wu; Tong Liu; et al. (Atmospheric Research, 2026)

Inhibition of postharvest soft rot in Chinese flowering cabbage by propyl gallate - Fengjun Li; Zhili Xu; Longlong Song; Lilang Li; Hai Liu; Yan Liao; Yuntao Zhao (Postharvest Biology and Technology, 2026)

Visible light photocatalytic enhanced heterogeneous cobalt catalyzed peroxymonosulfate synergistic process to degradation atrazine: Efficiency, influencing factors, by-products removal and mechanism - Qingkong Chen; Jieyu Xia; Fengjun Liu; Jianping Fan; Peng Yan; Mika Sillanpää (Journal of Environmental Sciences, 2026)

Preparation of mesoporous polydopamine/thyme essential oil/fish scale gelatin photothermal antibacterial film and its application on cherry tomato preservation - Yunfeng Yang; Quanwen Liu; Peng Yang; Xiulian Li; Xiangquan Zeng; Fengjun Guo; Xinguang Fan (Food Chemistry, 2026)

Physiological and transcriptomic insights into low temperature-induced suppression of internal browning in postharvest pineapple (Ananas comosus L.) - Longlong Song; Zhili Xu; Fengjun Li; Hai Liu; Lilang Li; Yan Liao; Yuntao Zhao (Postharvest Biology and Technology, 2025)

Effects of fermentation on the quality, flavor, and bacterial community changes of Longtian Zharou-a traditional Chinese fermented meat product - Aihua Lou; Xiping Jin; Zhuoqi Dong; Yaodong Wei; Yanyang Wu; Fengjun Xiao; Wei Quan; Yan Liu; Qingwu Shen; Jie Luo; Lei Zhou (Innovative Food Science & Emerging Technologies, 2025)

Functional characterization of two CCL20 chemokines in black rockfish (Sebastes schlegelii): dual roles in immune cell recruitment and direct antimicrobial defense - Fengjun Lin; Yiying Liu; Chonghui Chen; Xiaoxu Zhang; Pei Zhang; Huijun Huo; Chao Li; Qiang Fu (Fish & Shellfish Immunology, 2025)

A scalable layered stack reactor enables rapid self-formation of partial denitrification/anammox granular sludge - Hao Tan; Jinjin Zheng; Xuehai Yue; Enling Tian; Junxi Liu; Hong Liu; Shun Lu; Fengjun Yin (Chemical Engineering Journal, 2025)

A WRKY transcriptional factor, BrWRKY70, involves in stem lignification in postharvest Chinese flowering cabbage by regulating lignin synthesis - Fengjun Li; Ling Wang; Meiting Wu; Yulong Chen; Lilang Li; Hai Liu (Postharvest Biology and Technology, 2025)

Low-field NMR-based deep learning for non-destructive quality assessment of frozen model foods - Qiyong Jiang; Meng Liu; Zhaosheng Wang; Rentang Zhang; Yuxiao Wang; Fengjun Guo; Qing Sun; Cuirong Ren (Food Chemistry, 2025)

Synergistic acceleration of proton migration in osmotic microbial fuel cell: hydrophilic nanochannels coupling acid-base pairs created by functionalized metal-organic frameworks in forward osmosis membrane - Enling Tian; Yuan Liu; Cheng Song; Xingzu Wang; Fengjun Yin; Ling Fang; Shun Lu; Yu Lei; Hong Liu (Water Research, 2025)

Genome-wide identification of the C2-domain abscisic acid-related (CAR) protein family in Rosaceae and functional characterization of PbrCAR1 in pear pollen tube growth - Xueying Liu; Yanhong Zhang; Hong Su; Baofeng Zhang; Fengjun Zhao; Hao Zhang; Chao Tang; Peng Wang; Shaoling Zhang; Wenjie Zhou; Juyou Wu (Planta, 2025)

Unveiling interactions between anammox and denitrification from long-term steady-state scale and transient kinetic scale in a granular sludge system - Hao Tan; Fengjun Yin; Jinjin Zheng; Xuehai Yue; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Hong Liu (Bioresource Technology, 2025)

Preparation of emulsions with resveratrol to form functional coatings: Effect on yellowing of frozen limes during storage - Qiyong Jiang; Meng Liu; Zhaosheng Wang; Rentang Zhang; Yuxiao Wang; Fengjun Guo; Qing Sun (Food Hydrocolloids, 2025)

Electrochemical nitrite sensing using mass transfer signal with a catalyst-free small-sized rotating disk electrode for wastewater monitoring - Fengjun Yin; Xiaohui Yang; Shun Lu; Hanlin Zhang; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Zhaoming Chen; Hong Liu (Water Research, 2025)

Modeling electron competition and pH factor interactions improve cognitions of nitrite accumulation during denitrification - Xuehai Yue; Fengjun Yin; Hao Tan; Junxi Liu; Lin Chang; Xiaohui Yang; Sha Wang; Ying Zhao; Haofei Shi; Wei Zhang; Hong Liu (Environmental Research, 2025)

Efficient Zn2+ transport tailoring by BiOIO3 nanosheets modified glass fiber separator toward ultra-stable Zn metal anodes - Zijun Feng; Yongle Liang; Fengjun Niu; Yu Liu; Qiying Zhang; Guobao Xu; Xiaolin Wei; Liwen Yang (Chemical Engineering Journal, 2025)

Effects of Environmentally Friendly Aquaculture Chamber Coatings on Enzyme Activities, Histology, and Transcriptome in the Liver of Larimichthys crocea - Xuan Xu; Huayu Song; Huicai Wu; Lu Zhang; Fengjun Lin; Chonghui Chen; Xiaoxu Zhang; Yiying Liu; Chao Li; Qiang Fu (Marine Biotechnology, 2025)

Near-freezing temperature alters ROS metabolism and gene transcription to enhance peach chilling tolerance and aroma quality - Hongru Liu; Hui He; Qiankun Wang; Shaozhen Li; Fengjun Guo; Changfeng Zhang; Ke Wang; Chenxia Liu; Chunfang Wang; Xiao Wang; Bingjie Chen; Yi Zhang; et al. (Food Research International, 2025)

Identification and Validation of Lipid Metabolism Gene FASN-Associated miRNA in Wilms Tumor - Xiaoqing Wang; Xiao Li; Lin Tan; Fengjun Zhang; Jing Zhang; Xu Zhao; Yongfei Zhang; Guoqiang Du; Wei Liu (Biochemical Genetics, 2025)

Accumulation characteristics and source analysis of microplastics derived traffic of soil in the Tibetan Plateau - Mengjie Liu; Tianjie Shao; Shengmei Han; Weige Nan; Ruiyuan Wang; Fengjun Xiao; Yudan Wang; Zhibao Dong; Yanhua Wang (Journal of Hazardous Materials, 2024)

L-glutamic acid-functionalized graphene oxide with characteristic of anti-stacking towards efficient adsorption-reduction removal of Cr(VI) - Yuxin Wang; Yueqi Chen; Fengjun Shan; Tingting Zhang; Zhenbin Zhang; Meijun Liu (Journal of Environmental Chemical Engineering, 2024)

The preparation of fish scale gelatin-polydopamine photothermal sterilization film and its application for storage of cherry tomato - Yunfeng Yang; Xiulian Li; Ting Zhang; Xiangquan Zeng; Fengjun Guo; Quanwen Liu; Xinguang Fan; Da-Peng Yang (Food Packaging and Shelf Life, 2024)

Deciphering the potential of potassium-ion batteries beyond room temperature - Weihao Xia; Fengjun Ji; Yunzhuo Liu; Zhen Han; Kaikai Li; Jingyu Lu; Wei Zhai; Deping Li; Lijie Ci (Science Bulletin, 2024)

Observation of Low-Level Jets in the Eastern Tropical Indian Ocean Based on Shipborne Coherent Doppler Lidar - Haiyuan Wang; Lin Liu; Mengqi Fan; Yang Yang; Guang Yang; Yongliang Duan; Baochao Liu; Qinglei Su; Binbin Zhang; Fengjun Wang; Xuliang Shi; Qiuchi Li; et al. (Journal of Ocean University of China, 2024)

Host-derived lactic acid bacteria alleviate short beak and dwarf syndrome by preventing bone loss, intestinal barrier disruption, and inflammation - Mandi Liu; Fengjun Xiang; Jialu Pan; Yongzhi Xue; Maoyuan Sun; Kuan Zhao; Wuchao Zhang; Baishi Lei; Peipei Gao; Limin Li; Wanzhe Yuan (Veterinary Microbiology, 2024)

Injectable exosome-loaded quaternized chitosan/oxidized sodium alginate hydrogel with self-healing, bioadhesive, and antibacterial properties for treating combined radiation-wound injury - Guanqun Peng; Jia Hu; Jinnan Guo; Jiahui Dong; Yuanyuan Zhao; Tong Ye; Fengjun Xiao; Zhiyun Meng; Hui Gan; Ruolan Gu; Peng Han; Wenzhong Sun; et al. (Chemical Engineering Journal, 2024)

HCMV IE1/IE1mut Therapeutic Vaccine Induces Tumor Regression via Intratumoral Tertiary Lymphoid Structure Formation and Peripheral Immunity Activation in Glioblastoma Multiforme - Xiaoli Yang; Shasha Jiang; Fengjun Liu; Zonghui Li; Wenxuan Liu; Xianjuan Zhang; Fulong Nan; Jun Li; Meng Yu; Yunyang Wang; Bin Wang (Molecular Neurobiology, 2024)
Glioblastoma multiforme (GBM), a highly malignant invasive brain tumor, is associated with poor prognosis and survival and lacks an effective cure. High expression of the human cytomegalovirus (HCMV) immediate early protein 1 (IE1) in GBM tissues is strongly associated with their malignant progression, presenting a novel target for therapeutic strategies. Here, the bioluminescence imaging technology revealed remarkable tumor shrinkage and improved survival rates in a mouse glioma model treated with HCMV IE1/IE1mut vaccine. In addition, immunofluorescence data demonstrated that the treated group exhibited significantly more and larger tertiary lymphoid structures (TLSs) than the untreated group. The presence of TLS was associated with enhanced T cell infiltration, and a large number of proliferating T cells were found in the treated group. Furthermore, the flow cytometry results showed that in the treatment group, cytotoxic T lymphocytes exhibited partial polarization toward effector memory T cells and were activated to play a lethal role in the peripheral immunological organs. Furthermore, a substantial proportion of B cells in the draining lymph nodes expressed CD40 and CD86. Surprisingly, quantitative polymerase chain reaction indicated that a high expression of cytokines, including chemokines in brain tumors and immune tissues, induced the differentiation, development, and chemokine migration of immune cells in the treated group. Our study data demonstrate that IE1 or IE1mut vaccination has a favorable effect in glioma mice models. This study holds substantial implications for identifying new and effective therapeutic targets within GBM.

Long-term nitrogen fertilization enhances crop yield potential in no-tillage systems through enhancing soil fertility - Shengping Li; Xueping Wu; Xiaojun Song; Xiaotong Liu; Huizhou Gao; Guopeng Liang; Mengni Zhang; Fengjun Zheng; Peng Yang (Resources, Conservation and Recycling, 2024)

Fast circulatory nitrification/denitrification process using continuous flow synchronous settling reactors promotes organic utilization efficiency in nitrogen removal - Fengjun Yin; Haotian Wei; Xuehai Yue; Hao Tan; Xiaohui Yang; Shun Lu; Sha Wang; Ying Zhao; Hong Liu (Chemical Engineering Journal, 2024)

Development of PEG-mediated genetic transformation and gene editing system of Bryum argenteum as an abiotic stress tolerance model plant - Fengjun Leng; Guiwei Zhou; Ruoyuan Shi; Chengyang Liu; Yirui Lin; Xinqiang Yu; Yanhua Zhang; Xiangxi He; Zhu Liu; Mingming Sun; Fang Bao; Yong Hu; et al. (Plant Cell Reports, 2024)

Single-Cell RNA Sequencing Transcriptomics Revealed HCMV IE2-Related Microglia Responses in Alzheimer’s-Like Disease in Transgenic Mice - Fengjun Liu; Zhifei Wang; Delei Niu; Xianjuan Zhang; Fulong Nan; Shasha Jiang; Jun Li; Meng Yu; Xiaoli Yang; Shuyun Zhang; Xiaoqiong Zhou; Hui Wang; et al. (Molecular Neurobiology, 2024)
Although multiple factors are known to concur with Alzheimer’s disease (AD), the relationship between human cytomegalovirus (HCMV) and AD-like disease is unclear. Here, we propose a hypothesis that HCMV immediate-early 2 (IE2) protein promotes microglia activation and thus leads to AD-like disease. We successfully constructed IE2 transgenic mice expressing IE2 in the hippocampus. Single-cell sequencing analysis revealed that IE2 promoted the activation of microglia and upregulated the expression of disease-associated microglia genes. Differentially expressed gene analysis and pathway enrichment revealed that IE2 upregulated immune and nervous system disease-related genes. Immunohistochemical analysis showed that the expressions of both amyloid precursor protein (APP) and p-Tau were significantly upregulated in the brains of IE2 mice and were markers of AD. Taken together, these findings provide useful insights into AD-like disease activated by HCMV IE2.

Newcastle disease virus suppresses antigen presentation via inhibiting IL-12 expression in dendritic cells - Fulong Nan; Wenlong Nan; Xin Yan; Hui Wang; Shasha Jiang; Shuyun Zhang; Zhongjie Yu; Xianjuan Zhang; Fengjun Liu; Jun Li; Xiaoqiong Zhou; Delei Niu; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Identification and stability evaluation of polyphenol oxidase substrates of pineapple fruit - Hai Liu; Jiangming Li; Yueming Jiang; Fengjun Li (Food Chemistry, 2024)

2D flake-like garnet electrolytes for solid-state lithium metal batteries - Jun Cheng; Yixuan Guo; Hongqiang Zhang; Fengjun Ji; Xuan Zhou; Zhen Zeng; Hongbin Liu; Qing Sun; Deping Li; Lijie Ci (Chemical Engineering Journal, 2024)

Strong links between aggregate stability, soil carbon stocks and microbial community composition across management practices in a Chinese dryland cropping system - Fengjun Zheng; Xiaotong Liu; Mengni Zhang; Shengping Li; Xiaojun Song; Bisheng Wang; Xueping Wu; Kees Jan van Groenigen (CATENA, 2023)

Holocene aeolian activity triggered by climate change and endorheic-exorheic drainage transition in the Headwater Region of the Yellow River, Tibetan Plateau - Guangyin Hu; Jingjing Hu; Lupeng Yu; Linhai Yang; Xiangjun Liu; Fengjun Xiao; Zhibao Dong (Geomorphology, 2023)

Positive effects of crop rotation on soil aggregation and associated organic carbon are mainly controlled by climate and initial soil carbon content: A meta-analysis - Fengjun Zheng; Xiaotong Liu; Weiting Ding; Xiaojun Song; Shengping Li; Xueping Wu (Agriculture, Ecosystems & Environment, 2023)

Human Cytomegalovirus IE2 Disrupts Neural Progenitor Development and Induces Microcephaly in Transgenic Mouse - Delei Niu; Xianjuan Zhang; Shuyun Zhang; Tianyu Fan; Xiaoqiong Zhou; Hui Wang; Xueming Zhang; Fulong Nan; Shasha Jiang; Fengjun Liu; Yunyang Wang; Bin Wang (Molecular Neurobiology, 2023)
Human cytomegalovirus (HCMV) is a significant contributor to congenital birth defects. Limited by the lack of animal models, the pathogenesis of neurological damage in vivo caused by HCMV infection and the role of individual viral genes remain to be elucidated. Immediate early (IE2) protein may play a function in neurodevelopmental problems caused by HCMV infection. Here, this study intended to investigate IE2’s long-term effects on development of the brain in IE2-expressing transgenic mice (Rosa26-LSL-IE2 +/− , Camk2α-Cre) aimed to observe the phenotype of postnatal mice. The expression of IE2 in transgenic mice was confirmed by PCR and Western blot technology. We collected mouse brain tissue at 2, 4, 6, 8, and 10 days postpartum to analyze the developmental process of neural stem cells by immunofluorescence. We discovered that transgenic mice (Rosa26-LSL-IE2 +/− , Camk2α-Cre) can reliably produce IE2 in the brain at various postpartum phases. Furthermore, we also observed the symptoms of microcephaly in postnatal transgenic mice, and IE2 can damage the amount of neural stem cells, prevent them from proliferating and differentiating, and activate microglia and astrocytes, creating an unbalanced environment in the brain’s neurons. In conclusion, we demonstrate that long-term expression of HCMV-IE2 can cause microcephaly through molecular mechanisms affecting the differentiation and development of neural stem cells in vivo. This work establishes a theoretical and experimental foundation for elucidating the molecular mechanism of fetal microcephaly brought by HCMV infection in throughout the period of neural development of pregnancy. Graphical Abstract

Tailoring the draw solution chemistry in the integrated electro-Fenton and forward osmosis for enhancing emerging contaminants removal: Performance, DFT calculation and degradation pathway - Lei Zheng; Yanfang Xiong; Yimeng Gao; Fengjun Yin; Mateusz Szczygiełda; Martyna Krajewska; Phong H.N. Vo; Changsheng Jiang; Hong Liu (Science of The Total Environment, 2023)

Which is the dominant source for the aeolian sand in the Badain Jaran Sand Sea, Northwest China: Fluvial or gobi sediments? - Aimin Liang; Zhengcai Zhang; Ivan Lizaga; Zhibao Dong; Yunfeng Zhang; Xiaokang Liu; Fengjun Xiao; Junliang Gao (CATENA, 2023)

Adaptive Graph-Learning Convolutional Network for Multi-Node Offshore Wind Speed Forecasting - Jingjing Liu; Xinli Yang; Denghui Zhang; Ping Xu; Zhuolin Li; Fengjun Hu (Journal of Marine Science and Engineering, 2023)
Multi-node wind speed forecasting is greatly important for offshore wind power. It is a challenging task due to unknown complex spatial dependencies. Recently, graph neural networks (GNN) have been applied to wind forecasting because of their capability in modeling dependencies. However, existing methods usually require a pre-defined graph structure, which is not optimal for the downstream task and limits the application scope of GNN. In this paper, we propose adaptive graph-learning convolutional networks (AGLCN) that can automatically infer hidden associations among multi-nodes through a graph-learning module. It simultaneously integrates the temporal and graph convolutional modules to capture temporal and spatial features in the data. Experiments are conducted on real-world multi-node wind speed data from the China Sea. The results show that our model achieves state-of-the-art results in all multi-scale wind speed predictions. Moreover, the learned graph can reveal spatial correlations from a data-driven perspective.

Reactive and microbial inhibitory mechanisms depicting the panoramic view of pH stress effect on common biological nitrification - Xuehai Yue; Hong Liu; Haotian Wei; Lin Chang; Zhengjun Gong; Lei Zheng; Fengjun Yin (Water Research, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

Facilitating proton transport by endowing forward osmosis membrane with proton conductive sites in osmotic microbial fuel cell - Enling Tian; Yuan Liu; Fengjun Yin; Shun Lu; Lei Zheng; Xingzu Wang; Zongping Wang; Hong Liu (Chemical Engineering Journal, 2023)

Experimental study on the treatment of desulfurization wastewater from coal-fired power plant by spray evaporation - Zongkang Sun; Ning Zhao; Yongxin Feng; Fengjun Liu; Chenjian Cai; Guangmin Che; Yaping Zhang; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Differences in Rice Productivity and Growth Attributes Under Different Paddy-Upland Cropping Systems - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Wanjun Ren (International Journal of Plant Production, 2022)

Removal of Hg2+ from desulfurization wastewater by tannin-immobilized graphene oxide - Heng Chen; Fengjun Liu; Chenjian Cai; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Incineration experiment of medical waste of novel coronavirus pneumonia (COVID-19) in a mobile animal carcass incinerator - Shaorui Zhang; Yanjun Zhang; Fengjun Wang; Da Kang; Jingjie Wang; Minghao Wang; Chunwei Zhang; Yongtang Wang; Hong Liu; Baodong Zhou; Yong Wu (Waste Disposal & Sustainable Energy, 2021)

Dental Pulp Stem Cell-Derived Extracellular Vesicles Mitigate Haematopoietic Damage after Radiation - Fanxuan Kong; Chu-Tse Wu; Panpan Geng; Chao Liu; Fengjun Xiao; Li-Sheng Wang; Hua Wang (Stem Cell Reviews and Reports, 2021)
Radiation therapy can cause haematopoietic damage, and mesenchymal stem cells (MSCs) derived extracellular vesicles (EVs) have been shown to reverse this damage. Our previous research showed that dental pulp stem cells (DPSCs) have a strong proliferation capacity and can produce abundant amounts of EVs to meet the requirements for use in vitro and in vivo. DPSCs derived EVs (DPSCs-EVs) are evaluated for their effect on reducing haematopoietic damage. Haematopoietic stem cell (HSC) numbers and function were assessed by flow cytometry, peripheral blood cell counts, histology and bone marrow transplantation. Epidermal growth factor (EGF) was used as a reference for evaluating the efficiency of EVs. miRNA microarray was employed to find out the changes of miRNA expression after cells being irradiated in vivo and the role they may play in mitigation the radiation caused injury. We observed the effect of DPSCs-EVs on promoting proliferation and inhibiting apoptosis of human umbilical vein endothelial cells (HUVECs) and FDC-P1 cells in vitro. We found that DPSCs-EVs and EGF could comparably inhibit the decrease in WBC, CFU count and KSL cells in vivo. We also verified that EVs could accelerate the recovery of long-term HSCs. In summary, DPSCs-EVs showed an apoptosis resistant effect on HUVECs and FDC-P1 cells after radiation injury in vitro. EVs from DPSCs were comparable to EGF in their ability to regulate haematopoietic regeneration after radiation injury in vivo. Radiation could alter the expression of some miRNAs in bone marrow cells, and EVs could correct these changes to some extent.

Residual nitrogen from preceding garlic crops is important for double-cropped rice - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Nkrumah Malik; Wanjun Ren (Nutrient Cycling in Agroecosystems, 2020)

Characteristics of vertical karst development and grouting reinforcement engineering practice of the Ordovician top in the Feicheng coalfield, China - Mei Qiu; Fengjun Huang; Jingxue Wang; Longqing Shi; Xingyue Qu; Tianhao Liu (Carbonates and Evaporites, 2020)

Important meteorological variables for statistical long-term air quality prediction in eastern China - Libo Zhang; Yongqiang Liu; Fengjun Zhao (Theoretical and Applied Climatology, 2018)

Novel deletion of SLC34A2 in Chinese patients of PAM shares mutation hot spot with fusion gene SLC34A2–ROS1 in lung cancer - Shang Dandan; Chen Yuqin; Lu Wei; Peng Ziheng; Zhou Dapeng; Yang Jianzhu; Xin Xin; Liu Yonghong; Tian Fengjun (Journal of Genetics, 2018)

Fenofibrate ameliorates diabetic retinopathy by modulating Nrf2 signaling and NLRP3 inflammasome activation - Qiuping Liu; Fengjun Zhang; Xian Zhang; Rui Cheng; Jian-xing Ma; Jinglin Yi; Jingming Li (Molecular and Cellular Biochemistry, 2018)

Complete mitochondrial genome of the Burmese Short-Tailed Shrew, Blarinella wardi (Mammalia, Soricidae) - Fengjun Li; Xuming Wang; Qi Zhang; Haijun Jiang; Haixue Wei; Qing Wang; Shunde Chen; Shaoying Liu (Conservation Genetics Resources, 2018)

The complete mitochondrial genome of Chinese Shrew, Sorex sinalis (Soricidae) - Xuming Wang; Fengjun Li; Qi Zhang; Haijun Jiang; Shunde Chen; Shaoying Liu (Conservation Genetics Resources, 2018)

Spatial and temporal variation of the near‐surface wind environment in the dune fields of northern China - Xujia Cui; Zhibao Dong; Hu Sun; Chao Li; Fengjun Xiao; Zhengyao Liu; Shaopeng Song; Xiaolan Li; Nan Xiao; Weiqiang Xiao (International Journal of Climatology, 2018)
Research on the wind environment provides an important reference for tackling desertification and related environmental issues in desert regions. This article examines spatial and temporal variation of the near‐surface wind environment in the dune fields of northern China, using data from 40 meteorological stations inside and around the dune fields. Wind speed series were first subjected to homogenization, with monthly mean wind speed of the highly correlated neighbour stations as reference series. We found that the homogenized wind speed trends were approximately in accordance with the raw wind speed trends. The wind environment showed spatial and temporal differences, but wind speed has generally decreased both annually and seasonally since 1960, with an average trend of −0.193 m s −1 decade −1 . Mean wind speed (1960–2014) and maximum wind speed (1975–2014) decreased significantly, with distinct seasonal differences. The decreasing trend depended strongly on a decreased wind of speeds >5 m s −1 and its frequency. Overall, 48.7–80.8% of the decrease resulted from decreases in the maximum wind speed. Thus, decreases in the maximum wind speed were the dominant change in the study area. We also found that two thirds of the decrease in the drift potential primarily resulted from decreases in three prevailing wind groups (northwest, west, and south winds). This resulted from changes in the East Asian monsoon and westerly circulation. Mean air and ground surface temperatures (1960–2014) increased significantly and were significantly negatively correlated with mean wind speed, whereas sunshine duration (1960–2014) decreased significantly and was significantly positively correlated with mean wind speed. Both correlations reveal that an increasing of atmospheric dust may be responsible for the weakened wind environment. However, China's widespread sand‐control and ecological construction projects have increased ground roughness.

Singular value decomposition analysis of spatial relationships between monthly weather and air pollution index in China - Libo Zhang; Yongqiang Liu; Fengjun Zhao (Stochastic Environmental Research and Risk Assessment, 2018)

Location characteristics and differentiation mechanism of logistics nodes and logistics enterprises based on points of interest (POI): A case study of Beijing - Guoqi Li; Fengjun Jin; Yu Chen; Jinjuan Jiao; Sijing Liu (Journal of Geographical Sciences, 2017)

Quantitative analysis of vascular parameters for micro-CT imaging of vascular networks with multi-resolution - Fengjun Zhao; Jimin Liang; Xueli Chen; Junting Liu; Dongmei Chen; Xiang Yang; Jie Tian (Medical & Biological Engineering & Computing, 2016)

Molecular characterization and expression analyses of ST8Sia II and IV in piglets during postnatal development: lack of correlation between transcription and posttranslational levels - Xi Zhu; Yue Chen; Nai Zhang; Zhiqiang Zheng; Fengjun Zhao; Ni Liu; Chunlong Lv; Frederic A. Troy; Bing Wang (Glycoconjugate Journal, 2015)

CRP Acts as a Transcriptional Repressor of the YPO1635-phoPQ-YPO1632 Operon in Yersinia pestis - Yiquan Zhang; Fengjun Sun; Huiying Yang; Lei Liu; Bin Ni; Xinxiang Huang; Ruifu Yang; Dongsheng Zhou (Current Microbiology, 2015)

Ecological stoichiometry of N:P:Si in China’s grasslands - Zhaoliang Song; Hongyan Liu; Fengjun Zhao; Chongyang Xu (Plant and Soil, 2014)

Spatial coupling analysis of regional economic development and environmental pollution in China - Li Ma; Fengjun Jin; Zhouying Song; Yi Liu (Journal of Geographical Sciences, 2013)

Quasi-plane-hypothesis of strain coordination for RC beams seismically strengthened with externally-bonded or near-surface mounted fiber reinforced plastic - Zhenhua Ren; Xiantao Zeng; Hanlong Liu; Fengjun Zhou (Earthquake Engineering and Engineering Vibration, 2013)

Evaluation and optimization of the spatial organization of the petrochemical industry in China - He Liu; Fengjun Jin; Yi Liu; Jinxue Ding; Xu Xu (Journal of Geographical Sciences, 2013)

Transportation development transition in China - Fengjun Jin; Jinxue Ding; Jiao’e Wang; Dong Liu; Chengjin Wang (Chinese Geographical Science, 2012)